Karakteristik Ibu Hamil Yang Mengalami Pre Eklampsia Di Rumah Sakit Umum Umi Barokah Boyolali - Winarno, Tri, Sulastri, SKp.,M.Kes, Endang Zulaicha S, SKp.,M.Kep (2016)
Background: Mortality of mother in Indonesia 2012 that was 359 every 100 thousand birth live. Pre-Eklampsia and eklampsia represent the cause of mother death. Pre-Eklamsia earn because of some factor like pregnancy age, mother age, parity, heavy increase of mother body, family history, previous mother disease history, history of twin pregnancy. Research Purpose: To identify the characteristic of pregnant women by pre-eklampsia in Public Umi Barokah Boyolali Hospital. Research Method: This research was descriptive research with retrospective approach. The sample taking technique in this research was total sampling. Research instrument was checklist. Research Result: Mother pregnancy age with pre-eklampsia mostly was at thrid trimester pregnancy that was 43 respondents (87,8%). Mother age with pre-eklampsia mostly was risk age that was 34 respondents. (69,4%). Mother parity with pre-eklampsia mostly was primipara that was 38 respondents (77,6%). Heavy increase of pregnant mother body with pre-eklampsia mostly was normally that was 37 respondents (75,5%). Pregnant mother family history with pre-eklampsia mostly was mother do not have the family pre-eklampsia history that was 36 respondents (73,5%). Disease history at the pregnant mother with pre-eklampsia mostly was the mother not have disease history that was 39 respondents (79,6%). History of twin pregnancy mostly the pregnant mother with pre-eklampsia mostly have not twin history pregnancy that was 47 respondents (95,9%). Conclusion: Mother pregnancy age with pre-eklampsia mostly was at thrid trimester pregnancy. Mother age with pre-eklampsia mostly was risk age. Mother parity with pre-eklampsia mostly was primipara. Heavy increase of pregnant mother body with pre-eklampsia mostly was normally. Pregnant mother family history with pre-eklampsia mostly was mother do not have the family pre-eklampsia history. Disease history at the pregnant mother with pre-eklampsia mostly was the mothers not have disease history. Histories of twin pregnancy mostly the pregnant mother with pre-eklampsia mostly have not twin history pregnancy.